Cavernous Hemangioma of Tongue: Management of Two Cases - V, Pranitha (J Clin Diagn Res, 2014)
Hemangiomas are benign tumours of infancy and childhood, most commonly located in the head and neck region and occur more frequently in the lips, tongue and palate. The treatment depends upon lesion location, size and evolution stage and the patient’s age. This paper describes the management of cavernous hemangioma in a 2 -year -old child and 14 -year -old child using different approaches.